Diversity of secondary metabolites from Genus Artocarpus (Moraceae) - ALIEFMAN HAKIM (Smujo International, 2010)
Abstract. Hakim A. 2010. The diversity of secondary metabolites from Genus Artocarpus (Moraceae). Nusantara Bioscience 2:146-156. Several species of the Artocarpus genus (Moraceae) have been investigated their natural product. The secondary metabolites successfully being isolated from Artocarpus genus consist of terpenoid, flavonoids, stilbenoid, arylbenzofuran, neolignan, and adduct Diels-Alder. Flavonoid group represents the compound which is the most found from Artocarpus plant. The flavonoids compound which is successfully isolated from Artocarpus plant consists of the varied frameworks like chalcone, flavanone, flavan-3-ol, simple flavone, prenylflavone, oxepinoflavone, pyranoflavone, dihydrobenzoxanthone, furanodihydrobenzoxanthone, pyranodihydrobenzoxanthone, quinonoxanthone, cyclopentenoxanthone, xanthonolide, dihydroxanthone.